Getting immunosuppression just right: the role of clinical biomarkers in predicting patient response post solid organ transplantation. Issue 12 (2nd December 2021) - Brunet, Mercè; Millán, Olga
ABSTRACT: Introduction: Actually, immunosuppression selection isn't based on individual immune alloreactivity, and immunosuppressive drug dosing is mainly based on the development of toxicity and the achievement of specific target concentrations. Since a successful outcome requires optimal patient risk stratification and treatment, several groups have evaluated candidate biomarkers that have shown promise in the assessment of individual immune responses, the prediction of personal pharmacodynamic effects of immunosuppressive drugs and the prognosis and diagnosis of graft outcomes.. Areas covered: This review includes biomarkers that the Scientific Community in Solid Organ Transplantation currently considers to have potential as diagnostic and prognostic biomarkers of graft evolution. We have focused on recent scientific advances and expert recommendations regarding the role of specific and non-specific pharmacodynamic biomarkers that are mainly involved in the T-cell-mediated response. Expert opinion: Integral pharmacologic monitoring that combines pharmacokinetics, pharmacogenetics and predictive pharmacodynamic biomarkers may provide crucial information and allow personal adjustment of immunosuppressive drugs at an early stage before severe adverse events ensue. Multicentre, randomized, prospective and interventional trials are needed to fine tune the established cut-off values for each biomarker and the optimal monitoring frequency for each biomarker and to accurately evaluate possible clinical confounding factors to enable correct clinical qualification.